Modification of the industrialization model in Latin America - Klaus Esser (CEPAL Review, 1985)
A part from its intrinsic value, this article has the added merit of providing a straight forward presentation of a prominent German scholars views on Latin American industrialization. It is divided into four chapters. The first two outline the main interpretations of this process from the 1930s up to the present, while the last two address the central issue of the modification of the predominant industrialization model. The author takes a critical view, not only in terms of a long-term historical perspective, but also of the policies implemented during recent years in response to the crisis, which are generally marked by “stabilization without creativity” and the hope of resuming economic growth with the help of direct foreign investment.